Those Who Leave and Those Who Stay: Features of Internationally Mobile vs. Domestic Students - Hovdhaugen, Elisabeth; Wiers-Jenssen, Jannecke (Journal of International Students, 2021)
In this paper, we investigated how internationally mobile students from Norway diverge from students in Norway regarding social background, grades obtained at upper secondary school, and motivation to study. Data from two comparable surveys were used, one relating to students abroad and one relating to domestic students. Results showed that, on average, mobile students were of higher social origin than domestic students, but this did not apply across all fields. In some subject fields, mobile students had higher grades than domestic students, while they were lower in others. Mobile students clearly demonstrated higher motivation than domestic students, even when controlling for subject field and background variables. In sum, we found that mobile students constitute a select group in several ways, most prominently regarding study motivation. This suggests that mobile students potentially represent a positive contribution to the learning environment in more ways than bringing diversity in cultural background.